Soil Test Crop Response based INM on Brinjal (Solanum melongena L.) for Optimizing Productivity, Fruit Quality and Economics in Indian Mollisols - and Pawan Kumar Pant, Pallavi Bhatt*, Sobaran Singh (Journal of the Indian Society of Soil Science, 2022)
Soil test crop response (STCR) based integrated nutrient management (INM) study was carried out for optimizing productivity and fruit quality of brinjal (Solanum melongena L.) at N.E. Borlaug Crop Research Centre, G.B. Pant University of Agriculture and Technology, Pantnagar during kharif season of 2019 in Mollisols of Uttarakhand, India. Response of brinjal in terms of yield and fruit quality parameters was studied at different fertility and yield targets. The experiment was conducted in randomized block design with 10 treatments consisting of general recommended dose (GRD), STCR based INM with and without farmyard manure (FYM) at 200 and 250 q ha-1 yield targets. The fruit yield was significantly superior under INM with 10 t FYM ha-1 at 250 q ha-1 yield target over GRD. Similar trend was also observed for various quality parameters where STCR computed doses with FYM proved significantly superior over GRD. The benefit: cost ratio was highest under treatment with 250 q ha-1, whereas the least was observed with application of 10 t FYM ha-1. The present study clearly established the superiority of STCR based INM for optimizing productivity and improving fruit quality.